Co-gasification of black liquor and pyrolysis oil at high temperature: Part 2. Fuel conversion. (1st June 2017) - Bach-Oller, Albert; Kirtania, Kawnish; Furusjö, Erik; Umeki, Kentaro
Highlights: Blends of black liquor (BL) and pyrolysis oil (PO) were studied in a drop tube. Blending PO into BL increased the gas yield and carbon conversion of the char. BL generated much less tar than a pine reference. Blending PO into BL strongly reduced the amount of tar. The combined results encourage co-gasification of BL and PO. Abstract: The efficiency and flexibility of the BL gasification process may improve by mixing BL with more energy-rich fuels such as pyrolysis oil (PO). To improve understanding of the fuel conversion process, blends of BL and PO were studied in an atmospheric drop tube furnace. Experiments were performed in varying atmosphere (5% and 0% CO2, balanced by N2 ), temperature (800–1400 °C), particle size (90–200 μm and 500–630 μm) and blending ratio (0%, 20% and 40% of PO in BL on weight basis). Additionally, pine wood was used as a reference fuel containing little alkali. The addition of PO to BL significantly increased the combined yield of CO and H2 and that of CH4 . BL/based fuels showed much lower concentration of tar in syngas than pine wood. Remarkably, the addition of PO in BL further promoted tar reforming in presence of CO2 . Unconverted carbon in the gasification residue decreased with increasing fractions of PO. Small fuel particles showed complete conversion at 1000 °C but larger particles did not reach complete conversion even at T = 1400 °C.